THE EFFECT OF TEACHER CERTIFICATION ON TEACHERS’ PERFORMANCE AT SMAN 21 KABUPATEN TANGERANG - Ah. Cahyadi (JIPIS, 2018)
AbstractThis research investigates the effect of teacher certification on the teachers’ performance in the form of qualitative study. The research was carried out in SMA N 21 Kabupaten Tangerang from August to October 2018. The sources of the data are events, informants, and written documents. The data are collected through naturalistic observation, in-depth interview, and document analysis. In analyzing the data, the writer uses interactive model analysis including reducing the data, presenting the data, and drawing conclusion. The result of the research shows that (1) the teachers at SMA N 21 Kabupaten Tangerang create teaching and learning activities which bring about fun and cooperative way of learning, use various interesting materials and media, and conduct evaluation that promotes students’ learning (2) although in general the teachers at SMA N 21 Kabupaten Tangerang can be considered as professional teachers, there are still some points which need improvement in order to conduct more effective teaching and learning process. They are: the lesson planning and the variety of teaching and learning activity. Based on the research findings, the writer concludes that the teacher certification gives a partial effect on the quality of teaching and learning process at SMA N 21 Kabupaten Tangerang.Keywords: teacher certification, teachers’ performance AbstrakPenelitian ini membahas pengaruh sertifikasi guru pada kinerja guru dalam bentuk studi kualitatif. Penelitian ini dilakukan di SMA N 21 Kabupaten Tangerang dari Agustus hingga Oktober 2018. Sumber data adalah peristiwa, informan, dan dokumen tertulis. Data dikumpulkan melalui observasi naturalistik, wawancara mendalam, dan analisis dokumen. Dalam menganalisis data, penulis menggunakan analisis model interaktif termasuk mengurangi data, menyajikan data, dan menarik kesimpulan. Hasil penelitian menunjukkan bahwa (1) guru-guru di SMA N 21 Kabupaten Tangerang menciptakan kegiatan belajar mengajar yang menghadirkan cara belajar yang menyenangkan dan kooperatif, menggunakan berbagai bahan dan media yang menarik, dan melakukan evaluasi yang mempromosikan pembelajaran siswa (2 ) walaupun secara umum para guru di SMA N 21 Kabupaten Tangerang dapat dianggap sebagai guru yang profesional, masih ada beberapa poin yang perlu ditingkatkan untuk melakukan proses belajar mengajar yang lebih efektif, yaitu: perencanaan pelajaran dan beragamnya pengajaran dan pengajaran. kegiatan belajar. Berdasarkan temuan penelitian, penulis menyimpulkan bahwa sertifikasi guru memberikan pengaruh parsial terhadap kualitas proses belajar mengajar di SMA N 21 Kabupaten Tangerang.Kata kunci: kinerja guru, sertifikasi guru